تقييم أداء تخديم المحتوى الثابت لدى مخدمات الويب - رضوان دنده; إبراهيم حلوم (Tishreen University, 2018)
The services provided by the Internet are increasing and the number of users, which they use it, is increasing, and that causes a tremendous pressure on the data centers to provide the servers needed to operate these services. This highlights the need to use all the resources of the server the optimal way to save the expenses and reduce the waste. The web service is considered as one of the most popular types of web services and that because of the web pages being the most online resource-intensive, and hence the importance of choosing the right operating system and the right web server to provide the services comes. In this research, the evaluation of three servers (nginx, apache, IIS) is done.  Ubuntu operating system, and windows operating system are used to run these servers, and Tests were performed in an Error-free network. تزداد الخدمات التي تقدمها شبكة الانترنت ويزداد عدد مستخدميها لتسبب ضغطاً هائلاً على مراكز البيانات لتأمين المخدمات اللازمة لتشغيل هذه الخدمات، ومن هنا يبرز الحاجة لاستخدام كامل موارد المخدم بالطريقة الأمثل لتوفير المصاريف وتقليل الهدر. تعتبر خدمة الويب من أكثر أنواع الخدمات الشبكية انتشاراً وذلك لأن صفحات الويب تعتبر من أكثر الموارد طلباً عبر شبكة الانترنت ومن هنا تأتي أهمية اختيار نظام التشغيل ومخدم الويب المناسبين للتخديم. في هذا البحث قمنا بتقييم عمل ثلاث مخدمات وهي apache، nginx وInternet Information Services (IIS)، وقد استخدمنا لتشغيل هذه المخدمات نظامي تشغيل Ubuntu Server وWindows Server وتمت الاختبارات في شبكة خالية من الأخطاء.